Edukasi Pemakaian Masker dan Face shield dalam Mencegah Penyebaran Covid-19 Kepada Pedagang Pasar Panorama Kota Bengkulu - Hendri Hestiawan; Agus Nuramal; A. Sofwan F. Alqap; Yossie Anggraeny M (Universitas Muhammadiyah Semarang, 2020)
Covid-19 has infected millions of people around the world, including Indonesia. Market traders who interact with many people are very vulnerable to Covid-19 transmission. This activity aims to provide education and assistance to the traders at Panorama Market of Bengkulu City to comply with the health protocols set by the government, such aswearing masks and face shields, especially for outdoor activities. This activity was also followed by the distribution of masks and face shields to traders at Panorama Market so that they could be used in their daily trading activities. The educational method used participatory action research using lectures, discussions, questions and answers, demonstrations, posters and banners. This educational activity is a collaboration between the Engineering Faculty of Universitas Bengkulu, Community Health Center Jembatan Kecil and Sahabat Psikologi of Bengkulu City. Educational materials include the introduction of Covid-19 and health protocols in the form of wearing masks and face shields. The evaluation of the activity used a questionnaire sheet to find out the participants knowledge before and after being given education. The results of the activity showed that the education provided by the facilitator canincrease the knowledge of market traders about Covid-19 and health protocols in the form of wearing masks and face shields in an effort to prevent the spread of Covid-19. Participants knowledge of Covid-19 increased from 50% to 85%, while the importance of wearing masks and face shields increased from 60% to 90% after being given education.Keywords: Covid-19, Face shield, Health protocol, Market trader, Mask